The prince warriors and the unseen invasion - Shirer, Priscilla, 1974-; Detwiler, Gina (Shrier, Priscilla Evans. Prince warriors, 2016)
"In this second book in The Prince Warriors trilogy, the Prince Warriors face new challenges on earth and in the unseen realm of Ahoratos. The enemy, angry about his last defeat, is targeting them with weapons and tactics they had never imagined, including the flaming Olethron. The kids must turn to Ruwach and the Source, who can give them more pieces of armor to help them stand strong against this deadly threat."--Amazon.com.